(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background: Along with general health and economic indices, policymakers are more dealing with the subjective well-being (SWB) of society as a criterion to evaluate their performance. Also, the increasing number of articles published in mainstream health economics journals approves that the importance of SWB is increasing. The aim of the study was to investigate the urban-outskirt difference in subjective well-being level among Tehran and Rasht dwellers as Iranian metropolises. Methods: The analysis of the study is based on a structured interview that has been carried out by a designed questionnaire with 451 people living in Tehran and Rasht selected by the stratified two-stage cluster sampling method in 2018. One of these study innovations is defining the relative SWB index, a proxy for SWB and happiness. As the second main contribution, we try to overcome data unreliability about income and wealth by defining a specific index for identifying the financial status of interviewees. A series of statistical techniques like Ordered Probit were used. Results: According to the results, the city dwellers have higher life satisfaction (5.23 out of 7) than outskirt dwellers (5.05) while keeping the other factors to be constant. Also, People who live in Rasht had a lower level of SWB (5.06) than Tehran dwellers (5.22). The impact of religious belief is positive on the SWB level. Conclusions: It is for several years that international reports show that Iranian people are not at a proper level of happiness. Having more financial satisfaction, and feeling more positive emotions should be considered across society. Besides, being the landlord has a statistically significant positive effect on city dwellers’ SWB. Keywords: Self-Assessments, Happiness, Urban Population, Personal Satisfaction.